A study of quality circle development - Howard, Jane Elizabeth (1986)
Quality circles are a form of group activity designed to impact on attitudes to work and to improve company performance. This study notes the introduction and rise in importance of this phenomenon in UK industry and sets out to examine the concept in operation. The quality circle is defined and explored and its aims and objectives are examined. The literature on quality circles is reviewed and is found to comprise mainly anecdotal articles written for management journals, although the amount of rigorous research is growing. Its place in wider management theory is then considered, focussing on a number of key areas which the quality circle can be said to span. The second part of the thesis describes the case study of quality circles in action at an electronics firm, which was the backbone of the three year research programme. A number of hypotheses were developed and they are discussed in turn. A research methodology was subsequently devised to throw light on the most significant of these hypotheses, using three main techniques - attitude survey, interview and group process observation. The resultant data is described and presented in tables to be found in the appendices. Conclusions are drawn about the quality circle programme under scrutiny. It was not thought prudent to generalise too far, but a number of less specific conclusions are expressed, together with suggestions for further work in the field which would generate useful results.